Continued Decay of HIV Proviral DNA Upon Vaccination With HIV-1 Tat of Subjects on Long-Term ART: An 8-Year Follow-Up Study - Sgadari, Cecilia; Monini, Paolo; Tripiciano, Antonella; Picconi, Orietta; Casabianca, Anna; Orlandi, Chiara; Moretti, Sonia; Francavilla, Vittorio; Arancio, Angela; Paniccia, Giovanni; Campagna, Massimo; Bellino, Stefania; et al. (Frontiers in Immunology, 2019)
Introduction: Tat, a key HIV virulence protein, has been targeted for the development of a therapeutic vaccine aimed at cART intensification. Results from phase II clinical trials in Italy (ISS T-002) and South Africa (ISS T-003) in cART-treated patients indicated that Tat vaccination promotes return to immune homeostasis and reduces the virus reservoir. Here we present data of 92 vaccinees enrolled in the ISS T-002 8-year extended follow-up study (ISS T-002 EF-UP, ClinicalTrials.gov NCT02118168). Results: Anti-Tat antibodies (Abs) induced upon vaccination persisted for the entire follow-up in 34/92 (37%) vaccinees, particularly when all 3 Ab classes (A/G/M) were present (66% of vaccinees), as most frequently observed with Tat 30 µg regimens. CD4+ T-cells increased above study-entry levels reaching a stable plateau at year 5 post-vaccination, with the highest increase (165 cells/µL) in the Tat 30 µg, 3x regimen. CD4 T-cell increase occurred even in subjects with CD4+ nadir ≤250 cells/µL, a predictor of poor response to cART, and was associated with a concomitant increase of the CD4+/CD8+ T-cell ratio, a prognostic marker of morbidity/mortality inversely related to HIV reservoir size. Proviral DNA load decreased over time, with a half-life of 2 years and an estimated 90% reduction at year 8 in the Tat 30 µg, 3x group. In multivariate analysis the kinetic and amplitude of both CD4+ T-cell increase and proviral DNA reduction were fastest and highest in subjects with all 3 anti-Tat Ab classes and in the 30 µg, 3x group, irrespective of drug regimens (NNRTI/NRTI vs PI). HIV proviral DNA changes from baseline were inversely related to CD4+/CD8+ T-cell ratio and CD4+ T-cell changes, and directly related to the changes of CD8+ T-cells. Further, HIV DNA decay kinetics were inversely related to the frequency and levels of intermittent viremia. Finally, Tat vaccination was similarly effective irrespective of the individual immunological status or HIV reservoir size at study entry. Conclusions: Tat immunization induces progressive immune restoration and reduction of virus reservoirs above levels reached with long-term cART, and represents an optimal vaccine candidate for cART intensification towards HIV reservoirs depletion, functional cure and eradication strategies.